PREVALENCE AND ASSOCIATED RISK FACTORS FOR DRUG ABUSE AMONG YOUTHS IN THE ILORIN EMIRATE, NIGERIA: IMPLICATIONS FOR SOCIAL WELFARE INTERVENTION - Abdulhameed, Abdussalam; Edirin Osazuwa, Fortune; Oseni, Jamiu; Damilare Emmanuel, Wemimo o (African Journal of Social and Behavioural Sciences, 2024)
This study focused on the prevalence and associated risk factors for drug abuse among youths in the Ilorin Emirate, Nigeria, and implications for social welfare intervention. The population of the study consisted of all people within the age cohort of youth who are involved in drug abuse in the study area using purposive sampling to select six organisations that are dealing with people who abuse psychoactive drugs within the area of study. The study used snowballing to draw forty (40) research participants from each organisation, totalling 240 participants. The structured questionnaires were content validated, and the Cronbach alpha formula was used to determine the internal consistency reliability coefficients of 0.74, 0.84, 0.79, and 0.81, respectively, were obtained from all the scales. The data collected were via descriptive statistics, such as frequency counts, percentages, pie charts, means and standard deviations. The findings revealed that alcohol, cannabis/marijuana, tramadol, cigarette/tobacco, and Arizona, among others, are the leading drugs commonly abused by youth and have adverse effects on users. Equally, the study shows that inadequate staffing and stigmatisation from the public are the major factors impeding effective social welfare intervention in the study area. On the basis of these findings, the study recommended that there is an urgent need to recruit more social workers and establish more social welfare organisations that are dealing with people who abuse one form of drug or another to increase the number of qualified personnel that can handle such cases.